OPTIMALISASI MANAJEMEN PEMELIHARAAN ALAT KESEHATAN PUSKESMAS DI KABUPATEN BATANGHARI - H, Risky Kusuma; Desmarini, Desmarini (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The lack of medical equipment maintenance management in Community Health Centers results in many devices being non-functional or damaged. Additionally, the absence of competent technical experts for maintenance shortens the economic lifespan of the equipment. This study aims to optimize the implementation of medical equipment maintenance management in, Community Health Center. This research uses a descriptive qualitative approach with a system analysis method (input, process, output) and a POAC management approach (Planning, Organizing, Actuating, Controlling). The analysis strategy to address the problem uses a SWOT analysis. Data collection was carried out through in-depth interviews, observation, and document review at the Health Office and four selected, Community Health Center in Batanghari Regency. It was found that medical equipment maintenance management has not been optimal due to the lack of competent electromedical technicians, limited budgets, and the absence of clear Standard Operating Procedures (SOP). The optimization of medical equipment maintenance can be achieved through a standardized work mechanism using SOP guidelines, making the maintenance of medical devices more structured. The creation of these medical equipment maintenance SOPs requires coordination between the, Community Health Center and the Health Office. ABSTRAKKurangnya manajemen pemeliharaan alat kesehatan di Puskesmas mengakibatkan banyaknya alat kesehatan yang tidak berfungsi atau rusak, serta tidak ada nya tenaga ahli yang berkompeten dalam pemeliharaan membuat umur ekonomis alat menjadi pendek. Penelitian ini bertujuan untuk mengoptimalkan penyelenggaraan manajemen pemeliharaan alat kesehatan di Puskesmas. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode analisis sistem (input, proses, output) dan pendekatan manajemen POAC (Planning, Organizing, Actuating, Controlling). Strategi analisis untuk mengatasi masalah menggunakan analisis SWOT. Pengumpulan data dilakukan melalui wawancara mendalam, observasi, dan telaah dokumen di Dinas Kesehatan serta empat Puskesmas terpilih di Kabupaten Batanghari. Ditemukan bahwa manajemen pemeliharaan alat kesehatan belum optimal karena ketiadaan tenaga teknis elektromedik yang kompeten, anggaran yang terbatas, serta belum adanya Standar Operasional Prosedur (SOP) yang jelas. Optimalisasi pemeliharaan alat kesehatan dilakukan dengan melalui mekanisme kerja yang terstandar dengan menggunakan panduan SOP, sehingga pemeliharaan alat kesehatan lebih terstruktur. SOP pemeliharaan alat kesehatan tersebut memerlukan koordinasi pembuatan antara Puskesmas dan Dinas Kesehatan.